Norway. Official publication for the Paris exhibition 1900. [With a pref. by S. Konow and K.K.E. Fischer. In collab with A.M. Hansen, H.H. Reusch, A. Steen a.o.] (Aktie-Bogtrykkeriet, 1900)
With bibliogrs. crd, graphs, ills, index and tabs.